Discovery of Novel Diagnostic Biomarkers for Common Pathogenic Nocardia Through Pan-Genome and Comparative Genome Analysis, with Preliminary Validation - Chaohong Wang; Xinmiao Jia; Ming Wei; Jun Yan; Qing Sun; Sibo Long; Maike Zheng; Yiheng Shi; Guanglu Jiang; Yan Zhao; Hairong Huang; Xinting Yang; et al. (Pathogens)
The aim of this study was to reveal diagnostic biomarkers of considerable importance for common pathogenic Nocardia, utilizing pan-genomic and comparative genome analysis to accurately characterize clinical Nocardia infections. In this study, complete or assembled genome sequences of common pathogenic Nocardia and closely related species were obtained from NCBI as discovery and validation sets, respectively. Genome annotation was performed using Prokka software, and pan-genomic analysis and extraction of Nocardia core genes were performed using BPGA software. Comparative genome analysis of these core genes with the validation-set gene sequences was then performed using BLAT, with a threshold of 30% amino acid coverage and identity, in order to distinguish specific core genes. Finally, candidate gene-specific primers were designed using Snapgene software and DNA samples were obtained from clinical Nocardia strains and closely related species for validation. The analysis identified eighteen core genes specific to Nocardia spp., four core genes specific to N. farcinica, and forty-six core genes specific to N. cyriacigeorgica. After rigorous clinical validation, one gene from Nocardia spp. and five genes from N. cyriacigeorgica were confirmed to have high specificity and therefore can be used as reliable biomarkers for accurate diagnosis of Nocardia infection. This pioneering research reveals diagnostic biomarkers of considerable significance, with the potential to substantially enhance the precise diagnosis of common pathogenic Nocardia infections, thereby laying the groundwork for innovative diagnostic methodologies in subsequent studies.